2018
DOI: 10.1038/s41538-018-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine milk fat globule membranes as a complementary food on the serum metabolome and immune markers of 6-11-month-old Peruvian infants

Abstract: This study builds on a previous study by this group in which 6–11-month-old Peruvian infants who were fed bovine milk fat globule membrane (MFGM) containing complementary food had significantly fewer episodes of infection-related bloody diarrhea relative to those consuming a control food (skim milk powder). Micronutrient deficiencies including zinc deficiency were prevalent in this study population. To understand the mechanism behind the health benefits of consuming MFGM, the serum metabolome and cytokine leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…These infants (6-11 months of age) displayed a decreased Th1 response that was attributed to lowered serum cytokine IL-2. Thus, this study further corroborates the immune outcomes found in the trial as the Th1 immune system is activated during infection [150]. In another study, Gurnida et al (2012) studied the effects of formula supplemented with a ganglioside-enhanced, MFGM-derived, complex milk lipid in term infants [151].…”
Section: Mfgm Formula Group Did Notsupporting
confidence: 81%
“…These infants (6-11 months of age) displayed a decreased Th1 response that was attributed to lowered serum cytokine IL-2. Thus, this study further corroborates the immune outcomes found in the trial as the Th1 immune system is activated during infection [150]. In another study, Gurnida et al (2012) studied the effects of formula supplemented with a ganglioside-enhanced, MFGM-derived, complex milk lipid in term infants [151].…”
Section: Mfgm Formula Group Did Notsupporting
confidence: 81%
“…When faced with an immune challenge, two key biological factors are involved in the intestinal defense response: the mucosal immune system and the gut microbiota (the latter will be discussed in the following section). A recent study reported that supplementation with bovine MFGM was able to enhance overall immunity and metabolism ( 10 ) which may explain the previously reported reduction in infection-related diarrhea ( 6 ). This section discusses potential mechanisms whereby components in the MFGM are able to regulate cellular events to enable maturation of the mucosal immune system, thereby improving infant health (Table 4 ).…”
Section: Function Of Mfg In Infant Gut Maturationmentioning
confidence: 97%
“…These variations reflect maternal factors including diet, environment, maternal genetics, and body composition, as well as the changing needs of the infant over the period of lactation (Figure 1 ). Recent research has shown a protective effect of MFGM against infectious diseases ( 6 , 7 ), in part through the modulation of the intestinal immune response and the gut microbiota ( 8 10 ). Although the underlying mechanism is not entirely clear, the MFGM harbors two forms of glycoconjugates (glycoproteins and glycolipids), which are thought to have antimicrobial, anti-inflammatory, and prebiotic functions in the gut ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these proteins are glycosylated which play an important role in biological function during the lactation period [13,25,26] and are diverse in different species. Several reports suggested that the structure and bioactive components of the MFGM play a crucial role in infant gut maturation, neurological development, modulating cholesterol and lipid uptake, immunity [40], and metabolism [41]. Moreover, the MFGM proteins may have an essential role in shaping gut microbial populations, which in turn may provide various health benefits including immune defense [42] and inflammatory diseases early in life [43,44].…”
Section: Discussionmentioning
confidence: 99%